Further evidence that reading ability is not preserved in Alzheimer's disease. - O'Carroll, R; Prentice, N; Murray, C; van Beck, M; Ebmeier, K; Goodwin, G (1995)
BACKGROUND: Pre-morbid intelligence level is routinely assessed in Alzheimer's disease using the National Adult Reading Test (NART). This practice is based on the assumption that pronunciation of irregular words remains unaffected by the disease process. Recent reports have suggested that reading ability may become compromised in moderately demented subjects. METHOD: Sixty-eight probably Alzheimer patients were classified into stages of severity (minimal, mild and moderate) using the Mini-Mental State Examination (MMSE). NART and demographic equations were used to estimate pre-morbid ability. RESULTS: A significant correlation emerged between dementia severity and reading ability, NART v. MMSE scores, r = 0.46, P < 0.01. When the total sample was subdivided into moderate, mild and minimal subgroups, significant between-group differences emerged, despite the groups being well matched for age, sex, and years of full-time education. Pre-morbid IQ, as estimated by demographic regression equations, did not correlate with dementia severity. CONCLUSION: NART performance is compromised in moderate Alzheimer disease, and the measure provides a serious underestimate of pre-morbid IQ in patients with an MMSE of 13 or less.